Assessing the impact on caregivers caring for patients with rare pediatric lysosomal storage diseases: development of the Caregiver Impact Questionnaire - Magdalena Harrington; Asha Hareendran; Anne Skalicky; Hilary Wilson; Marci Clark; Jaromir Mikl (SpringerOpen, 2019)
Abstract Background Capturing the impact of caring for patients with debilitating rare disease is important for understanding disease burden. We aimed to develop and validate an instrument to measure the impact on caregivers of caring for children with three lysosomal storage diseases (LSDs): metachromatic leukodystrophy (MLD), neuronopathic mucopolysaccharidosis type II (MPS II) and mucopolysaccharidosis type IIIA (MPS IIIA). Methods A draft instrument was developed based on targeted literature searches and revised through sequential qualitative interviews with caregivers of patients first with MLD (n = 16), then with MPS II (n = 22), and finally with MPS IIIA (n = 8). The instrument, which covered domains of physical, emotional, social and economic burden, was refined at each stage of development based on caregiver feedback. Saturation of major concepts was reached during concept elicitation (MLD and MPS II). Results It was confirmed that caring for a patient with an LSD impacts social functioning, emotional/psychological functioning, physical functioning, daily activities, and finances/work productivity. Results from cognitive debriefing of the draft questionnaires were considered during each round of interviews, resulting in a final set of items that caregivers found clear and easy to understand. The Caregiver Impact Questionnaire (CIQ) has 30 items in five domains: (1) social functioning (7 items); (2) impact on daily activities (5 items); (3) emotional/psychological functioning (10 items); (4) physical functioning (6 items); and (5) financial impact (2 items). Conclusions These findings demonstrate that the content of the CIQ is relevant for determining the impact of caring on caregivers of patients with MLD, MPS II and MPS IIIA.